Predicting xenobiotic metabolism: a computational approach mining LC–MS/MS data with SIRIUS and BioTransformer - Victoria Pozo Garcia; Mengqiu Zhang; Tuğçe S. Çobanoğlu; Kasper Holm; Paul Jennings; David A. Poole; Sofia Moco (Archives of Toxicology, 2026)

Nutrient environment improves drug metabolic activity in human iPSC-derived hepatocytes and HepG2 - Victoria Pozo Garcia; Tuğçe S. Çobanoğlu; Helen Sophie Hammer; Rita Carlota; Kasper Holm; Catherine Verfaillie; Oliver Poetz; Paul Jennings; Sofia Moco (Archives of Toxicology, 2025)
Induced pluripotent stem cells (iPSCs) have emerged as a transformative tool in regenerative medicine, in liver research. The perspective of a stable and functional source of hepatocytes has led to developing protocols for human iPSC-derived hepatocytes-like cells (HLCs). Yet, hepatic models remain one of most challenging systems to functionally reproduce with iPSCs, due to its resulting limited metabolic function. Using an adapted nutrient regimen, two human hepatocyte models were characterized: HLCs (derived from iPSCs) and metabolically active HepG2 (mHepG2, derived from the cell line HepG2), for their drug metabolism activity. In these cell systems, the transcriptome, proteome, and metabolome of 11 drug-relevant cytochrome P450 (CYP) isoenzymes were studied. A liquid chromatography–mass spectrometry (LC–MS)-based metabolomics approach, using model drugs as isoenzyme reporters, was applied, achieving a comprehensive overview of mHepG2 and HLCs drug metabolism. Drugs used in this study to characterize xenobiotic machinery were: bupropion (25 µM), phenacetin (30 µM), rosiglitazone (10 µM), diclofenac (75 µM), dextromethorphan (15 µM), chlorzoxazone (60 µM), midazolam (15 µM), benzydamine (15 µM), coumarin (250 µM) and 7-ethoxycoumarin (60 µM). Being HepG2 notorious for its limited metabolic capacity, our study raises mHepG2 as a highly performant cell model, with activity on 8 drug-metabolizing CYPs. Modulation by nutrient environment in improving metabolic function of in vitro models is here proven as a key determinant. Likewise, HLCs hold the widest CYP coverage at the transcript level and were able to cope with a wide variety of chemical insults, making them a promising model for personalized metabolic studies.

P18-72 Integration of Metabolomics and Transcriptomics, as well as Mitostress, CALUX Assays and Targeted Proteomics for an Improved Mechanism-based Hazard Characterization of Drug-induced Liver Injury - F. Zickgraf; L. Wijaya; T. de Boer; C. Budin; S. Moco; V. Pozo Garcia; O. Pötz; P. Ternes; V. Giri; B. van de Water; C. Gomes; H. Kamp; et al. (Toxicology Letters, 2025)

S14-03 Comparison of Metabolism and Transport of Thiabendazole in Human and Rat In vitroModels - O. KLatt; C. Gendre; N. Hager; U. Deppenmeier; E. Dubreil; J. Henri; L. Hegarat; S. Moco; P. Jennings; A. Wilmes (Toxicology Letters, 2025)

P11-04 In-depth xenobiotic metabolism characterization of human in vitro liver models for toxicology - V. Pozo; T. Su Çobanoğlu; H. Hammer; R. Carlota; K. Holm; C. Verfaillie; O. Poetz; P. Jennings; S. Moco (Toxicology Letters, 2024)

P06-23 Integration of metabolomics and transcriptomics for improved mechanism-based hazard characterization of drug-induced liver injury - F.M. Zickgraf; L. Wijaya; T. de Boer; C. Budin; S. Moco; V. Pozo Garcia; P. Ternes; V. Giri; C. Gomes; B. van de Water; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2024)